2011
DOI: 10.1111/j.1467-789x.2011.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of the effect of aerobic vs. resistance exercise training on visceral fat

Abstract: It is increasingly recognized that the location of excess adiposity, particularly increased deposition of visceral adipose tissue (VAT), is important when determining the adverse health effects of overweight and obesity. Exercise therapy is an integral component of obesity management, but the most potent exercise prescription for VAT benefit is unclear. We aimed to evaluate the independent and synergistic effects of aerobic exercise (AEx) and progressive resistance training (PRT) and to directly compare the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
199
3
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(251 citation statements)
references
References 60 publications
14
199
3
15
Order By: Relevance
“…Over recent years, a growing body of scientific knowledge strongly suggests that regular performance of aerobic and resistance training is a major factor in the prevention and treatment of cardiovascular disease including risk factors such as obesity, diabetes and blood lipid levels (23).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over recent years, a growing body of scientific knowledge strongly suggests that regular performance of aerobic and resistance training is a major factor in the prevention and treatment of cardiovascular disease including risk factors such as obesity, diabetes and blood lipid levels (23).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of combined endurance (E) and strength (S) training for the maintenance and development of physical fitness and body composition have been extensively investigated and their importance especially for sedentary and moderately active populations is well known (15,19,21,23,34). Over recent years, a growing body of scientific knowledge strongly suggests that regular performance of aerobic and resistance training is a major factor in the prevention and treatment of cardiovascular disease including risk factors such as obesity, diabetes and blood lipid levels (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore increased levels of daily physical activity should be simultaneously promoted. Although resistance training retains or improves the relative percentage of lean mass to total body, current evidence failed to detect a loss of fat mass of a similar magnitude to aerobic training which promotes fat mass loss together with beneficial changes in muscle tissue [97][98][99] . Studies evaluating efficacy of dietary restriction together with exercise program showed more favorable results (as weight loss rate and body composition improvement) compared to diet or exercise prescription alone [69] .…”
Section: Energy Balance Physical Activity and Dietary Restrictionmentioning
confidence: 93%
“…Current physical activity and exercise recommendations offer that the inclusion of aerobic exercise is essential for exercise programs for overweight/obesity management. [4] The American College of Sports Medicine (ACSM) suggests 150 to 250 min/week of aerobic physical activity with moderate-intensity for individuals with overweight and obese. [5] Although physical activity is commonly recommended to reduce overall obesity, the effect of exercise-induced weight loss on abdominal adiposity has been still investigated.…”
mentioning
confidence: 99%